Semen characteristics of pubertal West African dwarf rams fed pineapple waste silage as replacement for dried cassava peel (2014)
In the tropics, ruminants are raised on natural pastures which decline rapidly in quality and quantity during the dry season. This study assessed the reproductive performance of rams fed with cassava–peel–silage (CPS) blended with pineapple-waste (PW) on: scrotal circumference, testicular size and semen volume. Randomized complete block design with four treatments of PW at 0, 20, 40 and 60% w/w in Diets 1, 2, 3 and 4 were used. Each treatment had three replicates while semen was collected once from all replicates in the treatments. Rams were fed experimental diets for 56 days. Cassava-peel was substituted with PW at 0, 20, 40 and 60% w/w in Diets 1, 2, 3 and 4 respectively. Fresh PW were ensiled in plastic mini silos. Samples of freshly processed pineapple waste were taken on the day of ensiling and ensiled products were opened after 21 days to determine their nutritive value. All silage blends had colours from brown to yellow with pH values from 4.0 to 6.8. The scrotal diameter from 16.00cm to 21.40cm and scrotal length from 8.83cm and 12.75cm but did not differ significantly (P>0.05). The sperm motility of rams fed diets 4 and 1 was similar to rams fed other diets. Mean sperm volume, percentage livability and percentage sperm morphology were similar across treatments (P>0.05). It can be concluded that CPS blended with PW up to 60% showed no adverse effect on semen characteristics and fertility of the rams.